2019
DOI: 10.1155/2019/2926580
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Determination of Methylxanthines in Commercial Brands of Tea Using Ultra-High-Performance Liquid Chromatography-Mass Spectrometry

Abstract: Recently, chromatographic techniques have the potential to be greener in order to reduce the environmental impact. In this work, a new simple, sensitive, efficient, and green analytical method based on UHPLC-MS has been developed for a quick determination of methylxanthines including caffeine, theobromine, and theophylline in tea. Under the optimum conditions, a baseline separation has been achieved within 30 seconds, using isocratic elution consisting of 90% water and only 10% acetonitrile at 0.5 mL/min flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The data are shown in Table 1 and Figure S5 . The TP content of jasmine tea, black tea, and green tea are 5.80, 4.31, and 1.53 μg/g, respectively, but oolong tea and rabbit plasma are not detected, which is consistent with the previous reports [ 2 , 3 ]. Furthermore, high levels of theobromine and caffeine that are hundreds and thousands of times higher than TP are found in the four tea samples.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The data are shown in Table 1 and Figure S5 . The TP content of jasmine tea, black tea, and green tea are 5.80, 4.31, and 1.53 μg/g, respectively, but oolong tea and rabbit plasma are not detected, which is consistent with the previous reports [ 2 , 3 ]. Furthermore, high levels of theobromine and caffeine that are hundreds and thousands of times higher than TP are found in the four tea samples.…”
Section: Resultssupporting
confidence: 92%
“…Theophylline (1,3-dimethyl-7 H -purine-2,6-dione) (TP) is a dimethylxanthine derived from the xanthine purine base of alkaloid, which occurs naturally in most kinds of teas (jasmine tea, black tea, oolong tea, etc.) and cocoa beans in trace amounts [ 1 , 2 , 3 ]. TP is an important bioactive component of tea, which has various bioactivities at low doses [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, alkaloid estimation was conducted as per the method stated by Aqel et al . (2019) using an isocratic programme. Compounds were identified and quantified by retention time and the linear calibration curves of standard compounds.…”
Section: Methodsmentioning
confidence: 99%
“…While caffeine is one of the main components in coffee, several derivatives of caffeine, such as xanthin, have also been reported 31 . Furthermore, different amounts of caffeine compounds have been reported in green and roasted beans for both Arabica and Robusta coffee 32 . Therefore, the literature studies have indicated caffeine's antimicrobial activity as the primary compound and its minor composition.…”
Section: Fig 2: Antifungal Activity Of Instant Coffee At (20 40 60 and 80mg/ml) Against (A) A Niger And (B) A Flavus After 6 Days At 26 °mentioning
confidence: 99%